Comparison of nutritional value and microbiological status of new imported fish species on the German market. (4th April 2014) - Karl, Horst; Lehmann, Ines; Manthey‐Karl, Monika; Meyer, Carsten; Ostermeyer, Ute
Summary Proximate composition, fatty acid profile, other nutritional values and spoilage indicators were examined in the muscle meat of five species: barramundi (Lates calcarifer) from various origins, tilapia (Oreochromis spp.) of different qualities, cobia (Rachycentron canadum) and leather jacket (Aluterus monoceros) from the Pacific Ocean and Patagonian grenadier (Macruronus magellanicus) from South America. Lowest lipid contents (0.4% and 0.8%) were found in leather jacket and cobia. Leather jacket fillets had lowest protein (16.2%) and highest sodium chloride content (4.9%). Concentrations of ∑EPA + DHA were 0.1 g 100 g−1 for tilapia and leather jacket, 0.2 g 100 g−1 for barramundi and cobia and 0.7 g 100 g−1 for Patagonian grenadier. Barramundi and tilapia were characterised by high taurine content (215 and 276 mg 100 g−1 ww.), and cobia had only low levels (41 mg 100 g−1 ww.). Iodine contents were low and selenium levels varied between 303 and 570 μg kg−1 ww. No sign of spoilage was detected.